Pengaruh Pendapatan dan Ketahanan Ekonomi terhadap Tingkat Stres Petani Jagung Perempuan di Dusun Tanete Jeneponto - Handayani, Andi Asti; Supatminingsih, Tuti; Sudirman, Sudirman (ARZUSIN, 2026)
The high economic pressure experienced by women corn farmers in Tanete Hamlet, Jeneponto Regency, has the potential to affect stress levels in household life and agricultural activities. This study aims to analyze the effect of income and economic resilience on the stress levels of women corn farmers. This study used a quantitative approach with a cross-sectional survey design. The research sample consisted of 30 respondents selected using a purposive sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression with the assistance of the JASP application. The results show that economic resilience has a negative and significant effect on stress levels, whereas income does not have a partially significant effect. Simultaneously, income and economic resilience have a significant effect on stress levels. The conclusion of the study affirms that household economic resilience is an important factor in reducing the stress levels of women corn farmers. The implications of this study provide theoretical contributions to the development of studies on household economics and the welfare of women farmers, as well as practical implications for village governments, community empowerment institutions, and relevant stakeholders in designing economic empowerment and social support programs for women farmers.